Global Trends in Climate-Smart Agriculture Research in Publications from 2010 to 2024 - Loso Judijanto (West Science Agro, 2026)
This study explores global trends in Climate-Smart Agriculture (CSA) research from 2010 to 2024, providing a comprehensive bibliometric analysis of publication growth, thematic evolution, and collaboration networks. The analysis reveals a significant shift in CSA research, with a growing focus on mitigation, technological innovations, and sustainable agricultural practices. Key themes such as soil carbon management, greenhouse gas emissions, and climate-resilient crops have emerged as central research areas, reflecting the growing need for climate adaptation and emission reduction strategies. The research highlights the leading roles of countries like India, China, and African nations such as Kenya, Ethiopia, and Malawi, in shaping CSA solutions. The study also emphasizes the increasing importance of international collaborations, which facilitate knowledge-sharing and the development of context-specific CSA practices. However, gaps in research remain, particularly in the areas of socioeconomic factors, policy frameworks, and scaling mechanisms for CSA adoption. Addressing these gaps is critical for ensuring the broader implementation and effectiveness of CSA strategies in the face of climate challenges.